(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
The present study is conducted to investigate heat and fluid flow in an open channel having a circular heater on the bottom surface under magnetic field. The semi-circle is heated isothermally and the other walls of the channel are kept adiabatic. The consequent mathematical model is governed by the coupled equations of mass, momentum and energy and solved by employing Galerkin weighted residual method of finite-element technique. A wide range of pertinent parameters such as Rayleigh numbers (Ra), and Hartmann numbers (Ha) are considered in the present study. In addition, the mixed convection regime is occurred due to buoyancy and shear forces. Various characteristics such as streamlines, isotherms and heat transfer rate in terms of the average Nusselt number (Nuav), average fluid temperature (?av), and Drag force (D) is investigated for the aforesaid parameters. The magnetic field is found as a control parameter on heat and fluid flow, particularly at higher Rayleigh numbers. It is observed that Hartmann numbers have a significant effect on average Nusselt number, average fluid temperature and Drag force. DOI: http://dx.doi.org/10.3329/jname.v9i2.8020 Journal of Naval Architecture and Marine Engineering 9(2012) 81-90